Structure and electrical properties of potassium-doped siloxane-poly(oxypropylene) ormolytes - Chaker, J.; Dahmouche, K.; Briois, V; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Judeinstein, P. (Kluwer Academic Publ, 2003)
The structure and the ionic conduction properties of siloxane-poly(oxypropylene) (PPO) hybrids doped with different potassium salts (KCF3SO3, KI, KClO4 and KNO2) are reported for two polymer molecular weights (300 and 4000 g/mol), labelled PPO300 and PPO4000, respectively. The doping concentration, related to the concentration of the ether type oxygen of the PPO chain, is the same whatever the salt and verifies [O]/[K] = 20. Ionic room temperature conductivity shows the highest value for the KCF3SO3 doped PPO4000 hybrid (4 x 10(-7)Omega(-1).cm(-1)). The structure of these hybrids was investigated by X-ray powder diffraction (XRPD) and X-ray absorption spectroscopy (EXAFS and XANES) at the potassium K-edge (3607 eV). XRPD results show that the hybrid matrix is always amorphous and the formation of secondary potassium phases is observed for all the samples, except for the KCF3SO3 doped PPO4000 hybrid. EXAFS results evidence a good correlation between the ionic conductivity and the presence of oxygen atoms as first neighbours around potassium.
Keywords: siloxane-PPO hybrids; solid ionic conductor; EXAFS; XANES